Roles of Organohalide-Respiring Dehalococcoidia in Carbon Cycling - Yi Yang (American Society for Microbiology, 2020)
ABSTRACT The class Dehalococcoidia within the Chloroflexi phylum comprises the obligate organohalide-respiring genera Dehalococcoides, Dehalogenimonas, and “Candidatus Dehalobium.” Knowledge of the unique ecophysiology and biochemistry of Dehalococcoidia has been largely derived from studies with enrichment cultures and isolates from sites impacted with chlorinated pollutants; however, culture-independent surveys found Dehalococcoidia sequences in marine, freshwater, and terrestrial biomes considered to be pristine (i.e., not impacted with organohalogens of anthropogenic origin). The broad environmental distribution of Dehalococcoidia, as well as other organohalide-respiring bacteria, supports the concept of active halogen cycling and the natural formation of organohalogens in various ecosystems. Dechlorination reduces recalcitrance and renders organics susceptible to metabolic oxidation by diverse microbial taxa. During reductive dechlorination, hydrogenotrophic organohalide-respiring bacteria, in particular Dehalococcoidia, can consume hydrogen to low consumption threshold concentrations (<0.3 nM) and enable syntrophic oxidation processes. These functional attributes and the broad distribution imply that Dehalococcoidia play relevant roles in carbon cycling in anoxic ecosystems.